Genetic ancestry, skin pigmentation, and the risk of cutaneous squamous cell carcinoma in Hispanic/Latino and non-Hispanic white populations - Eric Jorgenson; Hélène Choquet; Jie Yin; Thomas J. Hoffmann; Yambazi Banda; Mark N. Kvale; Neil Risch; Catherine Schaefer; Maryam M. Asgari (Communications Biology, 2020)
Eric Jorgenson and Hélène Choquet et al. find that northwestern European genetic ancestry is associated with increased risk of cutaneous squamous cell carcinoma (cSCC) in non-Hispanic whites, and more so in Hispanic/Latinos of the US. The ancestry effect is largely, but not entirely explained by genetic determinants of skin pigmentation in both populations.